The role of hydrogen in the energy transition of the oil and gas industry - Kai Zhang; Liu He; Liangliang Jiang; Shu Jiang; Ruyang Yu; Hon Chung Lau; Congjiao Xie; Zhangxin Chen (Energy Reviews)
Hydrogen, primarily produced from steam methane reforming, plays a crucial role in oil refining, and provides a solution for the oil and gas industry's long-term energy transition by reducing CO2 emissions. This paper examines hydrogen’s role in this transition. Firstly, experiences from oil and gas exploration, including in-situ gasification, can be leveraged for hydrogen production from subsurface natural hydrogen reservoirs. The produced hydrogen can serve as fuel for generating steam and heat for thermal oil recovery. Secondly, hydrogen can be blended into gas for pipeline transportation and used as an alternative fuel for oil and gas hauling trucks. Additionally, hydrogen can be stored underground in depleted gas fields. Lastly, oilfield water can be utilized for hydrogen production using geothermal energy from subsurface oil and gas fields. Scaling up hydrogen production faces challenges, such as shared use of oil and gas infrastructures, increased carbon tax for promoting blue hydrogen, and the introduction of financial incentives for hydrogen production and consumption, hydrogen leakage prevention and detection.